Fenomena Perilaku Konsumsi Mahasiswa Dilihat Dari Literasi Keuangannya - Septiana, Aldila (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2014)
ABSTRACT: This research aims to reveal the consumption behavior of university student Class C program sharia economics generation of 2012 at the University of Trunojoyo Madura as seen from the financial literacy of university student. This research use a qualitative research and design-phenomenology. The research data taken form questionnaire results, the recordings of interview, and record interviews at the time of the study. Data analysis of qualitative research start from data reduction, data display, conclusion drawing/ verification. Checking the validity of data use a source triangulasi and member check technique. The result showed that the consumption behavior university student Class C program sharia economics generation of 2012 in the University of Trunojoyo Madura seen from the financial literacy take of six informants, four of them rational and two irrational informants. Consumption behavior of rational and irrational university student Class C program sharia economics generation of 2012 at the University of Trunojoyo Madura is effect of family, friendship, economic conditions, and attitudes and beliefs of financial literacy of course. Description of financial literacy held university student Class C program sharia economics generation of 2012 at the University of Trunojoyo Madura is 1) high financial literacy; 2) medium financial literacy; and 3) low financial literacy.Keywords: consumption behaviors, financial literacy